2023
DOI: 10.3390/foods12234261
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Occurrence of Bioactive Peptides in Different Types of Cheeses

Adriano Henrique do Nascimento Rangel,
Débora América Frezza Villar de Araújo Bezerra,
Danielle Cavalcanti Sales
et al.

Abstract: The search for improvements in quality of life has increasingly involved changes in the diet, especially the consumption of foods which, in addition to having good nutritional value, are characterized by offering health benefits. Among the molecules that trigger several beneficial responses are peptides, which are specific fragments of proteins known to produce positive effects on the human body. This review aimed to discuss the bioactive potential of peptides from cheeses. Studies show that the protein compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Many reviews have been reported about metabolites' antimicrobial effect resulting from fermentation with lactic acid bacteria. 1,9,29–32 However, bacteriocins 33–35,37 and phenyllactic acid 6,36 stand out as antimicrobial agents of interest that could be present in fermented foods and fermentates. 27,38,39…”
Section: Antimicrobial Activity Of Fermentatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reviews have been reported about metabolites' antimicrobial effect resulting from fermentation with lactic acid bacteria. 1,9,29–32 However, bacteriocins 33–35,37 and phenyllactic acid 6,36 stand out as antimicrobial agents of interest that could be present in fermented foods and fermentates. 27,38,39…”
Section: Antimicrobial Activity Of Fermentatesmentioning
confidence: 99%
“…Challenges in production and purication of selected metabolites: implications for food applications Many reviews have been reported about metabolites' antimicrobial effect resulting from fermentation with lactic acid bacteria. 1,9,[29][30][31][32] However, bacteriocins [33][34][35]37 and phenyllactic acid 6,36 stand out as antimicrobial agents of interest that could be present in fermented foods and fermentates. 27,38,39 Several reports isolate and test the antimicrobial activity of LAB and examine their potential as bacteriocins producers.…”
Section: Antimicrobial Activity Of Fermentatesmentioning
confidence: 99%
“…However, it also affects the flavor of cheese through the formation of peptides and free amino acids. Large peptides do not contribute directly to the cheese flavor, but shorter peptides have varying degrees of characteristic bitterness, many of them being bioactive [14]. The peptidases and proteinases that catalyze proteolysis come from several major sources, namely the coagulant (pepsin, proteinases found in Rhizomucor, Cryphonectria parasitcia or Cynara cardunculus), the milk itself (e. g. plasmin, the intrinsic proteinase in milk), lactic acid starters and other secondary inoculants (e. g. Propionibacterium freudenreichii, Penicillium roqueforti, Penicillium camemberti), as well as from the complex Gram-positive bacterial microflora formed on the surface of cheeses, and, in some cases, exogenous peptidases or proteinases added to milk or curd to accelerate ripening.…”
Section: Introductionmentioning
confidence: 99%